2018
DOI: 10.2147/copd.s167192
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum IL-17 and decreased serum IL-10 and IL-35 levels correlate with the progression of COPD

Abstract: PurposeThis study aimed to measure the serum levels of interleukin (IL)-17, IL-10, and IL-35 in patients with stable chronic obstructive pulmonary disease (COPD) and disclose the correlations between their expression levels and clinical factors of patients.MethodsA total of 75 patients with stable COPD (47 males and 28 females) and 30 healthy controls (15 males and 15 females) were included in this study. The serum levels of IL-17, IL-10, and IL-35 were determined by enzyme-linked immunosorbent assay. The corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 36 publications
(57 reference statements)
3
27
0
1
Order By: Relevance
“…As shown in Figure 2, the levels of Th1 (TNF-α), Th2 (IL-17E), and Th17 (IL-17A and IL-22) cell cytokines at admission were significantly higher than those at discharge, and IL-22 and TNF-α exhibited the most significant changes with 2.8-fold and 2.0-fold increases, respectively. IL-10 content was low both during AEs and at the 120-day follow-up, indicating a defective IL-10 response in COPD patients, as previously reported [16]. No significant differences in sputum levels of cytokines were observed among different GOLD stages.…”
Section: Sputum Levels Of T Helper Cell Cytokines During Hospitalizationsupporting
confidence: 80%
See 1 more Smart Citation
“…As shown in Figure 2, the levels of Th1 (TNF-α), Th2 (IL-17E), and Th17 (IL-17A and IL-22) cell cytokines at admission were significantly higher than those at discharge, and IL-22 and TNF-α exhibited the most significant changes with 2.8-fold and 2.0-fold increases, respectively. IL-10 content was low both during AEs and at the 120-day follow-up, indicating a defective IL-10 response in COPD patients, as previously reported [16]. No significant differences in sputum levels of cytokines were observed among different GOLD stages.…”
Section: Sputum Levels Of T Helper Cell Cytokines During Hospitalizationsupporting
confidence: 80%
“…Studies have shown that high levels of TNF-α and IL-17A are negatively correlated with pulmonary function in COPD [12,15,16]. However, therapies targeting these cytokines (infliximab and etanercept against TNF-α and CNTO 6785 against IL-17) have not shown promising effects in COPD patients, such as an improvement in pulmonary function and symptom scores or a decrease in exacerbations [17][18][19][20][21].…”
mentioning
confidence: 99%
“…Several studies have demonstrated similar findings to ours. For example, Jiang et al 53 showed in their study that serum levels of IL-17 were considerably higher in patients with worse severity of disease (stages GOLD III and IV), relating to the progression of the disease. Additionally, Zou et al 54 found that serum IL-1β and IL-17 levels were significantly higher in patients with COPD than in the healthy control group.…”
Section: Discussionmentioning
confidence: 99%
“…68 Moreover, decreased IL-35 levels were negatively correlated with the smoking status, indicating that IL-35 can serve as a biomarker to estimate progression of chronic obstructive pulmonary disease. 69 The above results suggest that IL-35 may be a good indicator of allergic inflammation and can be used as a biomarker.…”
Section: Il-35 and Allergic Airway Diseasementioning
confidence: 81%
“…In addition, studies have shown that the expression of IL‐35 is down‐regulated in chronic obstructive pulmonary disease, a chronic bronchitis and emphysema characterized by airflow obstruction . Moreover, decreased IL‐35 levels were negatively correlated with the smoking status, indicating that IL‐35 can serve as a biomarker to estimate progression of chronic obstructive pulmonary disease . The above results suggest that IL‐35 may be a good indicator of allergic inflammation and can be used as a biomarker.…”
Section: Il‐35 and Immune‐related Diseasesmentioning
confidence: 83%